Efektivitas Kinerja Pegawai Negeri Sipil (PNS) Dalam Pengelolaan Pariwisata Dan Kebudayaan Di Kabupaten Karawang - Nurahman, Arif; Fadli, Uus Muhammad Darul; Khalida, Laras Ratu (Peneliti.net, 2023)
This research was conducted because there were several performances that had not met the targets of the Department of Tourism and Culture, where the focus under study was performance focus and would be directed at how the level of Accountability, Responsiveness and Responsibility in developing the Effectiveness of the performance of Civil Servants in tourism management and Culture in Karawang Regency. The research method used is descriptive with a qualitative method approach. Respondents amounted to three people, namely: Head of Tourism and Culture Office of Karawang Regency, Head of Sub-Coordinator of General Affairs and Personnel and Staff of Karawang Inventory and Cultural Needs. Data were collected by means of interviews, observation, and documentation studies. The results showed that the effectiveness of employee performance at the Karawang Tourism and Culture Office was in accordance with the emphasized aspects, namely Accountability, Responsiveness and Responsibility which were in accordance with the conditions and facts in the field.